The analysis of technical design of special effects in three chosen musical theatres at Istana Budaya / Mohd Kamil Zulkepeli - Zulkepeli, Mohd Kamil (2018)
Musical theatre is a type of theatre that showcases various elements of awe in its performances. Locals productions are non exceptional in this and most of them are now performing in Panggung Sari, Istana Budaya. Feedbacks towards musical theatres in Istana Budaya have becoming more extravagant as each performance portrays lots of magical elements and technical special effects (the designs of technical special effect that are mesmerizing). Research on technical designs (building structures and creation of technical special effect) and technical effects are intended to comprehend and analyze the technicalities of special effects such as building material, energy sources, method of implementation and the impacts of it in musical theatre production particularly in Istana Budaya. The data obtained were based on the three study material ("Aladdin the Musical", "Puteri Gunung Ledang the Musical" and "Cats the Musical") that have been analyzed and interpreted to answer and form the framework of the creation of a special effects design. The reference set of technical (creation of the technical form) that was produced includes the essence of a special technique in the production of a musical theatre in a musical theatrical production that has been used as a reference in the staging of musical theatre at Istana Budaya.